FPGA-Based Tactile Sensor Suite Electronics for Real-Time Embedded Processing - Oballe-Peinado, Óscar; Hidalgo-López, José Antonio; Castellanos-Ramos, Julián; Sánchez-Durán, José Antonio; Navas-González, Rafael Jesús; Herrán, Jaime; Vidal-Verdú, Fernando (IEEE, 2017)
Dexterity in robotic hands is not enough to cover the demands for more flexibility in the manufacturing process. Specifically, processes that involve cooperation or learning from humans, slippage detection and tactile feedback to improve grasp stability when different objects are manipulated, object exploration and classification, quality inspection, welding, etc. The sense of touch is the key to the capabilities of human hands, so tactile sensors must be incorporated into robotic hands to improve them. However, tactile sensing technology is not yet mature enough to be an effective tool. One reason for this limited performance is the need of acquisition and processing of large amounts of data in the short time required to perform a fluent manipulation. Smart tactile sensors can help in this goal if they are able to carry out local acquisition and processing of tactile data and transmit only relevant information through buses that guarantee bounded latency. FPGAs are devices which are especially suitable for this task due to their ability for parallel processing. This paper presents the realization of electronics for a tactile sensor suite based on FPGAs that implements a direct interface with the raw sensor and serial communication between the fingertips and palm.
Keywords: Tacto; Detectores; Intelligent sensors; Field programmable gate arrays; Robot tactile systems